Fiqh dakwah Syaikh Mushthafa Masyhur; penerjemah, Abu Ridho...[et.al]; penyunting, M. Badawi, M. Lili N. Aulia - MASYHUR, Mushthafa, Syaikh; Abu Ridho; Badawi, M; Aulia, Lili N (Dar At-Tauzi wa annasyr Al-Islamiah, 2005)
...jilid ; 24 cm